Plasma membrane and nuclear phosphatidylinositol 4,5-bisphosphate signalling in cancer - Chytła, Agnieszka; Rattay, Stephanie; Akgül, Baki; Sztacho, Martin (Lipids in health and disease, 2025)
The development of metastasis is a leading cause of cancer-related death that involves specific changes in the plasma membrane (PM) and nucleus of cancer cells. Elevated levels of membrane lipids, including sphingomyelin, cholesterol, and phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2), in the PM, contribute to changes in membrane rigidity, lipid raft formation, and actin polymerisation dynamics, processes that drive cell invasion. This review discusses the relationship between well-studied cytoplasmic phosphoinositides and their lesser-known nuclear counterparts, highlighting their functional role in metastatic progression. Nuclear phosphoinositides, particularly PI(4,5)P2, are essential for regulating transcription factors and chromatin organisation, thereby shaping gene expression patterns. We also explore the role of PI(4,5)P2 and its metabolism in cancer cell invasiveness and metastasis, proposing a model in which the dysregulation of cytosolic and/or nuclear PI(4,5)P2 pool triggers malignant transformation. Understanding the PI(4,5)P2-related mechanisms underlying metastasis may provide insights into potential therapeutic targets, paving the way for more effective therapies and improved patient outcomes.
Keywords: metastázy nádorů; Metastasis; signální transdukce; buněčné jádro; Cell Membrane; Phosphatidylinositol 4,5-Diphosphate; Signal Transduction; fosfatidylinositol-4,5-difosfát; Phosphatidylinositol 4,5-bisphosphate; Biocondensates; Neoplasms; Cell Nucleus; Neoplasm Metastasis; zvířata; Humans; membránové mikrodomény; Cancer; nádory; Membrane Microdomains; buněčná membrána; HPV; lidé; Nucleus; Animals